An Assessment of Entrepreneurial Ecosystem in Vietnam - Hoa Do, Lien Thi; Hang Hoang, Phuong Vo (Universitas Prasetiya Mulya, 2024)
The paper approached the quantitative analysis such as FGLS to assess the relevance of the factors of the entrepreneurial ecosystem. The data were exploited for seven locations in Vietnam from 2011 to 2020. The results show that market size, infrastructure, policies, human capital, science and technology have a statistically significant impact on entrepreneurial ecosystem. Of which, market size and infrastructure placed the greatest impact on the ecosystem. In addition to the model, time dummy variable was added to examine the impact of the time period after 2016 to the ecosystem, and the variable was proved to have a statistically significant effect on the ecosystem. The results also revealed the fact that the progress of the ecosystem require the synchronous development of entrepreneurial components.